OP0223 EFFICACY AND SAFETY OF E6011, AN ANTI-FRACTALKINE MONOCLONAL ANTIBODY, IN MTX-IR PATIENTS WITH RHEUMATOID ARTHRITIS. (June 2019) - Tanaka, Yoshiya; Takeuchi, Tsutomu; Yamanaka, Hisashi; Nanki, Toshihiro; Umehara, Hisanori; Yasuda, Nobuyuki; Tago, Fumitoshi; Kitahara, Yasumi; Kawakubo, Makoto; Torii, Kentaro; Hojo, Seiichiro; Kawano, Tetsu; et al.
Abstract : Background: Fractalkine (CX3CL1, designated as FKN hereafter) is the sole member of the CX3C-chemokine which leads to dual actions, chemotaxis and cell adhesion for leukocytes expressing the cognate receptor, CX3CR1, during their migration. We have conducted clinical trials of E6011, a novel humanized anti-FKN monoclonal antibody, for patients with rheumatoid arthritis (RA) in Japan 1 . This is the first report of efficacy and safety results of E6011 from a Phase 2, multicenter, randomized, double-blind, placebo-controlled, parallel-group comparison study in RA patients inadequately responding to methotrexate (NCT02960438 ). Objectives: To evaluate efficacy and safety of three dose of E6011 compared with placebo. Methods: During the 24-week double-blind period, patients with moderately to severely active RA of inadequate response to MTX were randomly assigned to E6011 100 mg, 200 mg, 400/200 mg, or placebo groups at a 1:2:2:2 ratio. In the E6011 100 mg, 200 mg, and placebo groups, subjects received 100 mg, 200 mg, or placebo at Weeks 0, 1, 2, and every 2 weeks subsequently. In the E6011 400/200 mg group, subjects received 400 mg at Weeks 0, 1, 2, 4, 6, 8, 10 and then 200 mg every 2 weeks subsequently. Results: A total of 190 subjects (54 in the placebo group, 28 in the 100 mg group, 54 in the 200 mg group, 54 in the 400/200 mg group) received study drug. Of the 190 subjects, 169 completed and 21 discontinued study treatment prematurely during the 24-week double-blind period. The ACR20 response rate at Week 12 (non-responder imputation), the primary endpoint, was 37.0% in the placebo group, 39.3% in the 100 mg group, 48.1% in the 200 mg group, and 46.3% in the 400/200 mg group (not statistically significant), and statistically significant difference from placebo in ACR20 response rate was found in the 200 mg and 400/200 mg groups at Week 24 (35.2% for placebo, 39.3% for 100 mg, 53.7% for 200 mg, 57.4% for 400/200 mg). In addition, we focused on CD16+ monocytes which highly expressing FKN receptor/CX3CR1 as a blood biomarker that linked to the clinical response to E6011. The whole patient population was divided into 2 groups according to the median value of baseline CD16+ monocyte percentage (Median: 10.35%). Much clearer ACR20 response was observed in a dose dependent manner in the subjects who showed higher baseline CD16+ monocytes over the median at Week 24 (NRI) (30.0% for placebo, 46.7% for 100 mg, 57.7% for 200 mg, and 69.6% for 400/200 mg) although such fashion was obscure in the subjects below the median value. Adverse events that occurred in ≥5% of subjects in any E6011 group were nasopharyngitis, upper respiratory tract infection, stomatitis, bronchitis, back pain, pharyngitis, and dental caries. As a results, E6011 was well tolerated with no notable safety concerns at doses of 100, 200, and 400/200 mg when administered subcutaneously for 24 weeks. Conclusion: E6011 provided clinical improvements with a good safety profile in RA patients with inadequately responding to MTX. Especially, a higher efficacy of E6011 was suggested in patients with higher baseline CD16+ monocytes (%). This is the world-first evidence suggesting that a novel approach to target FKN/CX3CR1 interaction could be beneficial for RA. References: [1] Tanaka Y, et al., Mod Rheumatol (2018) 28, 58-65 Acknowledgement: The authors wish to thank the study investigators. Disclosure of Interests: Yoshiya Tanaka Grant/research support from: Abbvie, Astellas, Bristol-Myers Squibb, Chugai, Daiichi-Sankyo, Eisai, Mitsubishi-Tanabe, MSD, Ono, Taisho-Toyama, Takeda, Speakers bureau: Abbvie, Asahi-kasei, Astellas, Bristol-Myers Squibb, Chugai, Daiichi-Sankyo, Eli Lilly, Eisai, Glaxo-Smithkline, Janssen, Mitsubishi-Tanabe, Novartis, Pfizer Japan Inc, Sanofi, Takeda, UCB, YL Biologics, Tsutomu Takeuchi Grant/research support from: Astellas Pharma Inc, Chugai Pharmaceutical Co, Ltd., Daiichi Sankyo Co., Ltd., Takeda Pharmaceutical Co., Ltd., AbbVie GK, Asahikasei Pharma Corp., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Eisai Co., Ltd., AYUMI Pharmaceutical Corporation, Nipponkayaku Co. Ltd., Novartis Pharma K.K., Grant/research support from: AbbVie, Asahi Kasei, Astellas, AstraZeneca, AYUMI, Bristol-Myers Squibb, Chugai, Daiichi Sankyo, Eisai, Eli Lilly Japan, Janssen, Mitsubishi Tanabe, Nippon Kayaku, Novartis, Pfizer Japan Inc, Taiho, Taisho Toyama, Takeda, Teijin, Grant/research support from: Astellas Pharma Inc., Bristol Myers Squibb, Chugai Pharmaceutical Co., Ltd., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Santen Pharmaceutical Co., Ltd., Takeda Pharmaceutical Co., Ltd., Teijin Pharma Ltd., AbbVie GK, Asahi Kasei Pharma Corp., Taisho Toyama Pharmaceutical Co., Ltd., SymBio Pharmaceuticals Ltd., Janssen Pharmaceutical K.K., Celltrion Inc., Nipponkayaku Co. Ltd., and UCB Japan, Consultant for: Astra Zeneca K.K., Eli Lilly Japan K.K., Novartis Pharma K.K., Mitsubishi Tanabe Pharma Co., Abbivie GK, Nipponkayaku Co.Ltd, Janssen Pharmaceutical K.K., Astellas Pharma Inc., Taiho Pharmaceutical Co. Ltd., Chugai Pharmaceutical Co. Ltd., Taisho Toyama Pharmaceutical Co. Ltd., GlaxoSmithKline K.K., UCB Japan Co. Ltd., Consultant for: AbbVie, Asahi Kasei, Astellas, AstraZeneca, AYUMI, Bristol-Myers Squibb, Chugai, Daiichi Sankyo, Eisai, Eli Lilly Japan, Janssen, Mitsubishi Tanabe, Nippon Kayaku, Novartis, Pfizer Japan Inc, Taiho, Taisho Toyama, Takeda, Teijin, Consultant for: Astra Zeneca K.K., Eli Lilly Japan K.K., Novartis Pharma K.K., Mitsubishi Tanabe Pharma Co., Asahi Kasei Medical K.K., AbbVie GK, Daiichi Sankyo Co., Ltd., Bristol Myers Squibb, and Nipponkayaku Co. Ltd., Speakers bureau: Astellas Pharma Inc., Bristol Myers Squibb, Chugai Pharmaceutical Co., Ltd., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Santen Pharmaceutical Co., Ltd., Takeda Pharmaceutical Co., Ltd., Teijin Pharma Ltd., AbbVie GK, Asahi Kasei Pharma Corp., Taisho Toyama Pharmaceutical Co., Ltd., SymBio Pharmaceuticals Ltd., Janssen Pharmaceutical K.K., Celltrion Inc., Nipponkayaku Co. Ltd., and UCB Japan, Speakers bureau: AbbVie, Asahi Kasei, Astellas, AstraZeneca, AYUMI, Bristol-Myers Squibb, Chugai, Daiichi Sankyo, Eisai, Eli Lilly Japan, Janssen, Mitsubishi Tanabe, Nippon Kayaku, Novartis, Pfizer Japan Inc, Taiho, Taisho Toyama, Takeda, Teijin, Speakers bureau: AbbVie GK., Bristol–Myers K.K., Chugai Pharmaceutical Co. Ltd., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Astellas Pharma Inc, Diaichi Sankyo Co. Ltd., Eisai Co. Ltd., Sanofi K.K., Teijin Pharma Ltd., Takeda Pharmaceutical Co. Ltd., Novartis Pharma K.K., Hisashi Yamanaka Grant/research support from: AbbVie, Eisai, Bristol-Meyers, Novartis, Behringer, Astellas, Kaken, Nippon-Shinyaku, Pfizer, UCB, Ayumi, Ono, Daiichi-Sankyo, Taisyo-Toyama, Takeda, Tanabe-Mitsubishi, Chugai, Teijin Pharma, Torii, YLbio, Speakers bureau: Bristol-Meyers, Astellas, Pfizer, Daiichi-Sankyo, Takeda, Tanabe-Mitsubishi, Chugai, Teijin Pharma, YLbio, Toshihiro Nanki Grant/research support from: Chugai, Eisai, Takeda, Teijin, Eli Lilly, Bristol-Myers, AbbVie, Ono, Novartis, Asahikasei, Mitsubishi-Tanabe, Astellas, Ayumi, Pfizer, Daiichi Sankyo, Shionogi, Sanofi, Nippon Kayaku, Yutoku, Actelion, UCB, Bayer, Nihon Pharmaceutical., Consultant for: UCB, Eisai, Chugai, Ono, Gilead., Speakers bureau: Mitsubishi-Tanabe, Chugai, Eisai, Takeda, Astellas, Janssen, Eli Lilly, Ayumi, Pfizer, Asahikasei, Sanofi, Daiichi Sankyo, Otsuka, AbbVie, Ono, Teijin, Nippon Kayaku, UCB., Hisanori Umehara: None declared, Nobuyuki Yasuda Shareholder of: Eisai Co., Ltd., Employee of: KAN Research Institute, Inc. (subsidiary of Eisai Co., Ltd.), Fumitoshi Tago Employee of: Eisai Co., Ltd., Yasumi Kitahara Shareholder of: Eisai Co., Ltd., Employee of: Eisai Co., Ltd., Makoto Kawakubo Shareholder of: Eisai Co., Ltd., Employee of: Eisai Co., Ltd., Kentaro Torii Shareholder of: Eisai Co., Ltd., Employee of: Eisai Co., Ltd., Seiichiro Hojo Employee of: Eisai Co., Ltd., Tetsu Kawano Employee of: KAN Research Institute, Inc. (subsidiary of Eisai Co., Ltd.), Toshio Imai Shareholder of: Eisai Co., Ltd., Employee of: KAN Research Institute, Inc. (subsidiary of Eisai Co., Ltd.)